2018
DOI: 10.1021/acs.oprd.8b00145
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Flow Process for Reductive Deoxygenation of ω-Chloroketone in the Synthesis of Vilazodone

Abstract: A continuous flow process for the reductive deoxygenation of 3-(4-chlorobutanoyl)-1H-indole-5carbonitrile to 3-(4-chlorobutyl)-1H-indole-5-carbonitrile was developed using a continuous stirred tank reactor (CSTR) setup. The opportunity for process optimization as well as scale-up feasibility was investigated at a laboratory scale. Advantages of a continuous process such as increased product yield, minimized impurity formation, enhanced safety, and increased overall purity of the isolated material thereby avoid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…Finally, 15 and 16 were made to react together to obtain the target product vilazodone with a yield of 90.0%. 7,16 Based on the above preliminary results, three scale-up experiments were carried out (Table 3). Two 2 kg scale experiments and a 3 kg scale experiment were conducted, which proceeded smoothly to provide vilazodone with a 56.2% yield and 99.93% purity after recrystallization.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, 15 and 16 were made to react together to obtain the target product vilazodone with a yield of 90.0%. 7,16 Based on the above preliminary results, three scale-up experiments were carried out (Table 3). Two 2 kg scale experiments and a 3 kg scale experiment were conducted, which proceeded smoothly to provide vilazodone with a 56.2% yield and 99.93% purity after recrystallization.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The experimental results showed that the optimal reaction temperature was 100 °C, and the reaction time was 1.5 h to obtain the product 15 in 82.0% yield. Finally, 15 and 16 were made to react together to obtain the target product vilazodone with a yield of 90.0%. , …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to the previous systems, the agitation is performed by moving the whole reactor rather than only the agitator parts. Figure 12 shows one such system [31][32][33].…”
Section: Applications Of Advanced Cstr Technologiesmentioning
confidence: 99%
“…12 shows one such system. [31][32][33] Yao et al 33 presented a continuous approach to the phosphorylation of 2,2′-methylene-bis(4,6-di-tert-butyl)phenol, comparing both tubular reactors and ACR. One particularly challenging aspect of this synthesis is an insoluble side product, triethylamine hydrochloride, produced during phosphorylation.…”
Section: Applications Of Advanced Cstr Technologiesmentioning
confidence: 99%